UPAYA KELAB UMNO DALAM MENGEMBANGKAN PARIWISATA MALAYSIA DI INDONESIA - Putri D., Chatra Octavia; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Kelab Umno is an International Organization that is not under the auspices of the Government but the government involves the UMNO Club in Malaysia's Tourism activities in Indonesia. This study aims to determine the implementation of management functions of the functions of planning, organizing, moving and supervision in Tourism. This research uses qualitative research method with descriptive analysis. This research was conducted at Malaysian Consulate Building in Medan on Jl Pangeran Diponegoro no. 43, Madras Hulu, Medan Polonia Medan City, North Sumatera 20151. Data collection techniques used are by way of observation, interview and documentation. While the validity of the data that researchers use is to extend the participation, triangulation and reference adequacy. The results show that, UMNO clubs play a role in developing Malaysian tourism in Indonesia, which aims to improve the Malaysian economy. Keywords: UMNO Club, Tourism, Foreign Student Bureau